PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BODY LOTION SCARLET WHITENING (STUDI KASUS PADA MAHASISWA/I ANGKATAN 2019-2022 STIENAS BANJARMASIN) - Noor, Masrani; Suarniki, Ni Nyoman; Khasanah, Citra (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
Abstract, This research aims to analyze the influence of product quality and price on purchasing decisions for Scarlet Whitening Body Lotion (Case Study of 2019-2022 Stienas Banjarmasin Class Students). The research method used is quantitative. The population of this research is students from the 2019-2022 class of Stienas Banjarmasin 2022 who have used or are currently using Scarlett Whitening body lotion. The sample for this research consisted of 100 respondents. The results of this research show that product quality and price influence the decision to purchase Scarlet Whitening Body Lotion (Case Study of 2019-2022 Stienas Banjarmasin Class Students).